2017
DOI: 10.14260/jemds/2017/370
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Stillbirths in a Referral Hospital From Northeast India- A Record Based Study

Abstract: BACKGROUND A foetal death is defined as "death prior to the complete expulsion or extraction from its mother of a product of conception, irrespective of the duration of pregnancy; the death is indicated by the fact that after such separation the foetus does not breathe or show any other evidence of life, such as beating of the heart, pulsation of the umbilical cord, or definite movement of voluntary muscles" without specification of the duration of pregnancy. India has highest number of stillbirths in the worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…1 In a study carried out by the author in the same hospital, about 54.38% of stillbirth were premature. 9 In studies from Sweden, most stillbirths could be attributed to an aetiology. In those studies, more than 50% of stillbirths had identified aetiology including congenital malformation.…”
Section: Resultsmentioning
confidence: 99%
“…1 In a study carried out by the author in the same hospital, about 54.38% of stillbirth were premature. 9 In studies from Sweden, most stillbirths could be attributed to an aetiology. In those studies, more than 50% of stillbirths had identified aetiology including congenital malformation.…”
Section: Resultsmentioning
confidence: 99%